2011
DOI: 10.1097/mph.0b013e3181f46e3e
|View full text |Cite
|
Sign up to set email alerts
|

Development of T-cell Acute Lymphoblastic Leukemia in a Patient in Very Long Lasting Complete Remission of Juvenile Myelomonocytic Leukemia

Abstract: Juvenile myelomonocytic leukemia (JMML) occurs with an incidence of 1.2 per million children a year, and represents 18% to 30% of all myelodysplastic (MDS) and myeloproliferative (MPS) disorders in the age group below 15, being by far the most common MDS/MPS in children younger than 4 years. The only therapeutic approach which results in a definitive cure of patients with JMML is myeloablative chemo-therapy/radio-therapy, followed by allogeneic hematopoietic cell transplantation. Few cases of transformation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Our T-cell findings have notable parallels in JMML patients. Occasionally, these children acquire T-ALL either concurrently with their MPN or after the resolution of their myeloid disease [ 18 , 34 36 ]. Our observation of decreased naïve peripheral T cells and increased thymic precursors may provide a mechanistic explanation for this association.…”
Section: Discussionmentioning
confidence: 99%
“…Our T-cell findings have notable parallels in JMML patients. Occasionally, these children acquire T-ALL either concurrently with their MPN or after the resolution of their myeloid disease [ 18 , 34 36 ]. Our observation of decreased naïve peripheral T cells and increased thymic precursors may provide a mechanistic explanation for this association.…”
Section: Discussionmentioning
confidence: 99%
“…11 Others have reported long-term survival of JMML patients without the need for chemotherapy treatment or bone marrow transplant, and relief of symptoms by using immunosuppressive agents such as sirolimus, suggesting indolent autoinflammatory disease. 27,[35][36][37][38] Niemeyer et al 39 reported that 65% of JMML patients had hypergammaglobulinemia, and 22% had signs of autoimmunity, which are also features of RALD. Interestingly, although PTPN11 mutations result in constitutive activation of the RAS signaling pathway and are common in JMML 17,22 and Noonan syndrome, so far we have not identified PTPN11 mutations in any of the patients being evaluated for RALD.…”
Section: Discussion and Spectrum Of Diseasementioning
confidence: 99%
“…Given that RALD and its clinical overlap with JMML are likely underrecognized, some patients diagnosed with JMML may have an indolent disease more consistent with RALD. JMML patients have occasionally been reported to undergo spontaneous regression of proliferative myelomonocytic disease 27,[35][36][37] with persistence of autoimmune disease, B lymphocytosis, and RAS-mutated clones. 35 RAS activation can indeed alter selection patterns of autoreactive B cells and antibody production leading to autoimmune manifestations.…”
Section: Discussion and Spectrum Of Diseasementioning
confidence: 99%
“…Single cases of B‐ and T‐lymphoblastic leukemia/lymphoma occurring after remission of JMML, and JMML occurring after remission of B‐lymphoblastic leukemia have been reported in the literature, as summarized in Table . These cases pose intriguing questions regarding a possible clonal relationship between JMML and lymphoblastic leukemia arising in the same patient or whether the two events simply occur by chance.…”
Section: Discussionmentioning
confidence: 99%